Estimasi Dinamika Populasi dan Produktivitas Sapi Bali di Kabupaten Kepulauan Yapen, Propinsi Papua (Estimation of the Dynamics of Population and Productivity of Bali Cattle in Kepulauan Yapen Regency, Papua Province) - Karel Yohanis Samberi; Nono Ngadiyono; Sumadi (Sumadi) (Faculty of Animal Science, Universitas Gadjah Mada, 2010)
The objective of this research was to investigate the dynamics of population, productivity, and output of Bali cattle in region of Kepulauan Yapen Regency, Papua Province. The research was carried out for 3 months, started inJuly until September 2009. The materials included 103 farmers as the respondent and 211 heads of Bali cattle. The result showed that reproductive efficiency (RE) was 88.38%, natural increase (NI) 18.18% and net replacement ratevalue (NRR) of Bali cattle male and female were 234.28% and 189.59% each. The potency and compotition of Bali cattle being exported every year without disturbing the existing population was about 13.11% equal to 354 cattle,consist of the remains of replacement stock (male cattle) about 4.27% equal to 115 cattle, culled not productive cattle of 3.18% male equal to 86 cattle and 5.67% for female equal to 153 cattle. Dynamic population of Bali cattle from 2004 until 2008 increased 6.6% per year in average and in 2013 population is estimated to be 3,028 cattle with the potency of about 2,153 cattle.(Keywords: Male Bali cattle, Population dynamics, Productivity)